'I'm not entitled to be married in Germany? Am I German or am I not?' Narratives and discursive strategies of citizen sponsors in the German spousal migration context. Issue 1 (2nd January 2021) - Block, Laura
ABSTRACT: The state interferes with the intimate spheres of families and couples via family migration policies, which have grown increasingly restrictive in many European countries. Mixed-status couples engaging in spousal migration develop coping strategies in order to adapt to hurdles and overcome them. This article explores the under-researched perspectives of sponsor spouses on (family) migration policies. When interacting with authorities, politicians or counselling services, the sponsors often react discursively, using arguments relating to human rights, citizenship, membership as well as gender and marriage/family norms. Based on a qualitative analysis of case dossiers of a German NGO counselling mixed-status couples, the article explores the narratives and strategies developed by the (mostly White) German citizen sponsors, thereby analysing the ways they 'perform citizenship' at the crossroads of migration control, marriage and family norms, and membership.